2008
DOI: 10.1007/s10658-008-9353-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into components of partial disease resistance, determined in vitro, and the concept of types of resistance to Fusarium head blight (FHB) in wheat

Abstract: This work presents an analysis of the relationship between components of partial disease resistance (PDR) detected using in vitro detached leaf and seed germination assays, inoculated with Microdochium majus, and Fusarium head blight (FHB) resistance to Fusarium graminearum assessed using point inoculation, termed Type II resistance. Relationships between in vitro-determined PDR components and FHB resistance using techniques which inoculate the wheat spike uniformly, termed Type I resistance (incidence and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…The PDR component incubation period was highly related to FHB disease incidence while resistance detached in the seed germination assay related to a greater decline in the level of FDK and a smaller reduction in DON than would be expected from the reduction in FHB diseases on the wheat spike ( Browne, 2007 ). Browne (2009) showed that higher germination rates in the seed germination were greater FHB resistance measured by single point inoculation strongly related to resistance assessed in spike (Type II). In this report, FHB resistance determined by seed soaking or soak-dry methods did not predict Type I resistance or Type II resistance in adult plants.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The PDR component incubation period was highly related to FHB disease incidence while resistance detached in the seed germination assay related to a greater decline in the level of FDK and a smaller reduction in DON than would be expected from the reduction in FHB diseases on the wheat spike ( Browne, 2007 ). Browne (2009) showed that higher germination rates in the seed germination were greater FHB resistance measured by single point inoculation strongly related to resistance assessed in spike (Type II). In this report, FHB resistance determined by seed soaking or soak-dry methods did not predict Type I resistance or Type II resistance in adult plants.…”
Section: Discussionmentioning
confidence: 88%
“…Unfortunately, the evaluation of FHB resistance has been slow due to the necessity to avoid escapes by evaluating resistance in whole plants over several years and in environ- ment factors ( Browne and Cooke, 2004 ). Therefore, there has been interest in developing in vitro assays to provide methods for prescreening FHB resistance such as: detached leaf assay ( Browne et al, 2005 ; Browne and Cook, 2005b ; Browne, 2007 ; Diamond and Cooke, 1999 ), seedling resistance ( Mesterhazy, 1995 ; Snijders, 1990 ), seed germination assay ( Browne and Cook, 2005a ; Browne, 2007 , 2009 ), coleoptiles assay ( Li et al, 2010 ; Wu et al, 2005 ) and response to the Fusarium mycotoxin deoxynivalenol (DON) ( Buerstmayr et al, 1996 ). The detached leaf assay was successful in identification of an important component of the resistances of FHB in European wheat germplasm and may have utility as a mechanism for discrimination among different resistances in breeding program ( Browne et al, 2004 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1999, Steiner et al. 2004, Browne 2009). The correlation between disease severity and VFDK emphasizes the impact that disease severity has on kernel quality, and it highlights the interrelatedness of visual FHB metrics.…”
Section: Discussionmentioning
confidence: 99%
“…(2009) used spray and point inoculation to separately classify QTL associated with type I and type II resistance. Browne (2009) showed the relationship between various partial disease resistance components and FHB incidence and severity. He concluded that although type I and type II mechanisms generally relate to resistance, assuming that these two defense mechanisms function independently does not typically account for the full expression of resistance to FHB in wheat.…”
mentioning
confidence: 99%